2016
DOI: 10.18632/oncotarget.8082
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of cancer risk associated with rs2292832 in miR-149 and rs895819 in miR-27a: a comprehensive and updated meta-analysis

Abstract: The aim of this study is to provide a precise quantification for the association between miR-149 T > C (rs2292832) and miR-27a A > G (rs895819) and the risk of cancer. We conducted a systematic literature review and evaluated the quality of included studies based on Newcastle-Ottawa Scale (NOS). Pooled odds ratios (ORs) and corresponding 95% confidence intervals (95% CIs) were calculated to assess the strengths of the associations. We identified 40 studies for pooled analyses. Overall, the results demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 66 publications
(52 reference statements)
4
17
0
Order By: Relevance
“…In our meta-analysis, the rs895819 polymorphism was found to be associated with an increased risk of colorectal cancer in allele contrast model, homozygote model and recessive model. In addition, three latest publications reported similar results [ 50 52 ], which will make our conclusions more credible. Moreover, when analysis was stratified by ethnicity, a decreased cancer risk could be detected among Caucasians, indicating that the distinction in genetic backgrounds among different ethnic groups might have an impact on cancer susceptibility, which was in accordance with the results of five previously published studies [ 52 56 ] and further demonstrated the reliability of our results.…”
Section: Discussionsupporting
confidence: 80%
“…In our meta-analysis, the rs895819 polymorphism was found to be associated with an increased risk of colorectal cancer in allele contrast model, homozygote model and recessive model. In addition, three latest publications reported similar results [ 50 52 ], which will make our conclusions more credible. Moreover, when analysis was stratified by ethnicity, a decreased cancer risk could be detected among Caucasians, indicating that the distinction in genetic backgrounds among different ethnic groups might have an impact on cancer susceptibility, which was in accordance with the results of five previously published studies [ 52 56 ] and further demonstrated the reliability of our results.…”
Section: Discussionsupporting
confidence: 80%
“…Fifty-eight abstracts were retrieved after the search “miR-27a”, “polymorphism” and “cancer”, and 27 articles were identified as eligible studies. Among the 58, 10 articles were pooled analysis, commentary [ 32 41 ] and 3 articles were review papers [ 28 , 29 , 42 ], and 3 reports were cancer biology experimental studies [ 43 45 ]. Ten studies were excluded because they reported non-cancer disease [ 46 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on 17 case-control studies with 7,813 cases and 9,602 controls, our previous meta-analysis did not suggest any association between rs895819 and cancer susceptibility, while rs895819 was associated with a reduced cancer risk in heterozygous, dominant or additive model in Caucasians but not in Asians [ 33 ]. By pooling 19 studies (17 articles) involving 7,800 cases and 9,060 controls, a recent study by Feng et al, failed to find any associations between rs895819 polymorphism and cancer risk, while statistically significantly reduced cancer risks were found among Asians for dominant contrast and a subtly decreased risk was observed in the Caucasian population for heterozygous or additive contrast [ 29 ]. In the present study, by including 34 studies with almost twice number of subjects, we found that rs895819 was associated with increased cancer risk in recessive model for all population and Asians, but not Caucasians, suggesting a possible ethnic difference in the genetic and the environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐149 was downregulated in an in vitro osteoarthritis model upon inflammatory stimulation . The SNP rs2292832 in miR‐149 was shown to associate with breast cancer and ischemic stroke; however, its association with BMD in human has not been reported in literature so far.…”
Section: Mir‐snpsmentioning
confidence: 94%